Planktic foraminifera-bound organic nitrogen isotopic composition in contemporary water column and sediment trap. (January 2019) - Li, Da-Wei; Xiang, Rong; Wu, Qiao; Kao, Shuh-Ji
Abstract: Planktic foraminifera-bound organic nitrogen isotopes (FB-δ 15 N) archived in sediments provide an opportunity to reveal past changes in marine nitrogen cycling in the upper water column. However, detailed knowledge about living foraminifera FB-δ 15 N is still critically lacking. This study presents the FB-δ 15 N analysis of planktic foraminifera collected from plankton tows and sediment traps in the South China Sea and the Bay of Bengal. Tests of Globigerinoides sacculifer with- and without-sac like chamber from plankton tows showed almost identical FB-δ 15 N values, suggesting that high thermocline δ 15 N is not incorporated into the carbonate tests during gametogenic calcification. Sediment trap samples revealed that species dwelling in the upper euphotic zone, such as Globigerinoides sacculifer, contained slightly depleted FB-δ 15 N relative to the deeper-dwelling species, such as Orbulina universa and Globigerinella siphonifera . The three species also contained FB-δ 15 N similar to δ 15 N of the suspended particulate organic matter at corresponding dwelling depths. Our results confirm the increase in FB-δ 15 N from shallower-dwelling species to deeper-dwelling species and these FB-δ 15 N differences (Δ 15 Nvertical ) between shallower- and deeper-dwelling species may shed light on the nitrogen dynamics of the euphotic zone in the South China Sea, which is under the influence of the East Asian winter monsoon. Highlights: Modern planktic foraminifera tests were analyzed for FB-δ 15 N. G. sacculifer tests with-sac and without-sac exhibit similar FB-δ 15 N values. G. siphonifera has similar FB-δ 15 N value to δ 15 N of shallow thermocline nitrate. FB-δ 15 N differences among species may illuminate euphotic nitrogen dynamics.